2020
DOI: 10.1016/j.jaci.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

IL-6–based mortality risk model for hospitalized patients with COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) has rapidly become a global pandemic. Because the severity of the disease is highly variable, predictive models to stratify patients according to their mortality risk are needed. Objective: Our aim was to develop a model able to predict the risk of fatal outcome in patients with COVID-19 that could be used easily at the time of patients' arrival at the hospital. Methods: We constructed a prospective cohort with 611 adult patients in whom COVID-19 was diagnosed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
122
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 27 publications
24
122
0
8
Order By: Relevance
“…Through comparing the cytokine levels in the serum samples of COVID-19 patients at longitudinal timepoints during severe illness or at recovery, we have identified differential cytokine profiles potentially associated with COVID-19 disease status. Besides IL-6, which has been reported as a potential biomarker for COVID-19 patients ( 28 , 40 ), we found that both IL-6 and IL-8 serum levels were elevated in COVID-19 patients with severe diseases. In particular, we found that serum levels of IL-6 and IL-8 were significantly higher in COVID-19 patients as compared with heath donors with the AUC, which represents the combination of detecting sensitivity and specificity, at 0.84 and 0.98, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…Through comparing the cytokine levels in the serum samples of COVID-19 patients at longitudinal timepoints during severe illness or at recovery, we have identified differential cytokine profiles potentially associated with COVID-19 disease status. Besides IL-6, which has been reported as a potential biomarker for COVID-19 patients ( 28 , 40 ), we found that both IL-6 and IL-8 serum levels were elevated in COVID-19 patients with severe diseases. In particular, we found that serum levels of IL-6 and IL-8 were significantly higher in COVID-19 patients as compared with heath donors with the AUC, which represents the combination of detecting sensitivity and specificity, at 0.84 and 0.98, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…To characterize the immunologic response in SARS-CoV-2 infection manifesting with different grades of severity, we measured the concentration of 66 biomarkers associated with monocyte/macrophage, inflammasome, NF-κB, and neutrophil activation; T cell activation and/or polarization; type I IFN and IFN response gene induction; endothelial integrity; and sepsis severity in the peripheral blood of COVID-19 patients and compared them with levels in healthy American volunteers (HVs). Cytokine and chemokine levels can vary considerably in their longitudinal trajectories during the course of COVID-19 as a function of the phase of the disease and receipt of immunomodulatory medications ( 15 , 25 ). Therefore, we focused our initial analysis on 119 patients who underwent the first blood sampling within the initial 7 days of hospitalization ( Supplemental Table 1 and Supplemental Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… 11 In covid-19, an increased level of interleukin 6 and C reactive protein correlates with disease severity and mortality. 12 13 Thus, blocking interleukin 6 activity might play a role in mitigating the inflammatory response and improve clinical outcomes in patients with covid-19. To test this hypothesis, we conducted a randomised controlled trial comparing tocilizumab plus standard care with standard care alone in patients admitted to hospital with severe or critical covid-19.…”
Section: Introductionmentioning
confidence: 99%